From Enron to Worldcom and Beyond: Life and Crime After Sarbanes-Oxley - Kathleen F. Brickey (Washington University Law Quarterly, 2003)
This Article presents the alternative view that the Sarbanes-Oxley Act’s criminal provisions make significant strides toward piercing the veil of corporate silence.
Keywords: Whistleblowing; Securities fraud; Criminal liability; Sentencing guidelines (Criminal procedure); Corporate reform; Corporate governance; Sarbanes-Oxley Act of 2002; United States